PENGEMBANGAN E-LEARNING PPPPTK SENI DAN BUDAYA YOGYAKARTA MENGACU SCORM - , Ceravina Susanti Kanisiastirin, Ir. P. Insap Santosa, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
As a training institution, PPPPTK Arts and Culture of Yogyakarta develops e-learning system in order to accomplish its duties and functions. The system is intended for educational access equity in order to reach more training participants and save the budget. Firstly, e-learning system is developed with material that has been standardized. It is intended to use the same material for each Learning Management System (LMS) so that the material can be shared. It is very important because an elearning material should be able to replace the function of teacher in a classroom and interact with the user. One of the standards that can be used is the standard of Advance Distributed Learning (ADL). This standard is Sharable Content Object Reference Model Distributed Learning (ADL) which provides a variety of specifications accomplished by LMS. The aim of this study is to develop e-learning system which fulfilled the SCORM standard especially on the content to be integrated into a variety of LMS or elearning system which support SCORM. The method used in this study is to convert the contents which had not been referring to the content-based SCORM into content based SCORM which uses open source tool (teaching material prototype for Diklat Produktif Kria Keramik). Content packet will be packed in Zip which contains a lot of assets and an IMSManifest.xml file. The content is then uploaded to the system. Utilization of SCORM standard on e-learning system PPPPTK Arts and Culture will provide added value and competitive advantage.